2015
DOI: 10.17507/tpls.0508.10
|View full text |Cite
|
Sign up to set email alerts
|

Problems of English Language Acquisition in Saudi Arabia: An Exploratory-cum-remedial Study

Abstract: Abstract-'An international language belongs to its users, not to the countries whose national languages have become internationalized' (Edge 1992). With an ever increasing number of L2 users it is time we rewrote the description of the place of English among world languages. All types of interactions, more particularly between nations, are through English, for a reason no other than the fact that it is the only language in which non native users can possibly communicate. It is the language of science, technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 4 publications
2
92
0
Order By: Relevance
“…A study conducted by Altwaijri (1982) revealed that the students from Saudi government schools have been studying English language since 10 years, but their performance is not satisfactory. Therefore, most of the students lack the skills and motivation of learning English language, who are admitted in university programs after passing from high schools (Alrashidi & Phan, 2015;Al-Nasser, 2015). There is an immediate need of conducting various academic projects and search for improved teaching qualities at the Saudi government schools to implement the objectives and aims of vision 2030.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Altwaijri (1982) revealed that the students from Saudi government schools have been studying English language since 10 years, but their performance is not satisfactory. Therefore, most of the students lack the skills and motivation of learning English language, who are admitted in university programs after passing from high schools (Alrashidi & Phan, 2015;Al-Nasser, 2015). There is an immediate need of conducting various academic projects and search for improved teaching qualities at the Saudi government schools to implement the objectives and aims of vision 2030.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Themain causes for low competence in the English language among students include teacher-centered instruction, traditional teaching methodologies, memorization, lack of motivation, lack of practice, customs and culture (Alrashidi& Phan, 2015). Other barriers to learning English in Saudi Arabia include the introduction of English at a later stage, mother tongue interference, heavy use of L1, shortage of teachers training, the constancy of curriculum and syllabus for long time and lack of Information and communication technology use (Al-Nasser, 2015).Saudi students' English language proficiency is among the worst in the world (Carfax Educational Projects, 2016). According to the EF English Proficiency Index, Saudi Arabia ranks 68 out of 72 countries observed (EF English Proficiency Index, 2017) (Table 3).…”
Section: Status Of Elt In Saudi Arabiamentioning
confidence: 99%
“…The following sections have identified some of the areas teachers may lack competency in and require professional development programs to up-grade their teaching skills. The article does not look for reasons for why teachers may not be adequately equipped for the classroom which can be traced back to the content of teacher education programs (Alhamzi, 2003;Al-Seghayer, 2014;and Al-Nasser, 2015). Rather we have focused on what is needed for in-service teachers now and in future years to improve the teaching and by effect learning of English throughout the Kingdom of Saudi Arabia.…”
Section: English Language Teaching Initiatives: 2013 -2015mentioning
confidence: 99%